The Santa Fe Trail : its history, legends, and lore - Dary, David (University Press of Kansas, 2012)
A prize-winning historian of the Old West brings to life the people who laid down the Santa Fe Trail and opened commerce with Spanish America. He uses first-hand accounts and contemporary records to give us a vivid recreation of a time and place crucial to America's westward expansion.